SOCIALIZATION OF DEVELOPMENT OF COMMUNITY-BASED EDUCATION QUALITY PLANNING SYSTEM IN EDUCATION UNITS IN GARUNGGUNG PESANTREN PACKAGE C SCHOOLS - Wahyudin, Undang Ruslan; Permana, Hinggil; Nurlailasari, Ella (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Education is an important foundation in building a cultured, knowledgeable, and competitive society. However, in the context of non-formal education, such as in Sekolah Paket C Pesantren Garunggung, challenges in developing the quality of education are often the main concern. This activity is a socialization program through lecture and question and answer methods that aim to introduce and implementing a community-based education quality planning system in education units in pesantren. This socialization involves educators, local stakeholders, and the pesantren community. This activity discusses concrete steps taken in the development of a community-based education quality planning system, starting from identifying needs to developing implementation models. The conclusion of this socialization is expected to increase awareness and a shared commitment to improve the quality of education, as well as strengthen community involvement in the education planning and development process. Thus, through the socialization of this seminar, the development of a community-based education quality planning system in Garunggung Islamic boarding schools becomes more accessible and connected to the needs and aspirations of the local education community.